Hepatocellular Cancer-Derived Alpha Fetoprotein Uptake Reduces CD1 Molecules on Monocyte-derived Dendritic Cells - Li, Chunlei (Cell Immunol, 2018)
Alpha fetoprotein (AFP) is produced by over 50% of hepatocellular carcinomas (HCC). Uptake of tumor-derived AFP (tAFP) can impair activity of human dendritic cells (DC). The expression pattern of the lipid antigen presenting genes from the CD1 family is reduced in AFP-treated monocyte-derived DC. Surface CD1 family proteins, particularly CD1d, were reduced in AFP-exposed DC (by both normal cord blood-derived AFP (nAFP) and tAFP). NKT cells recognize lipid antigens presented by CD1d molecules. They play an important role in connecting the innate and adaptive immune systems, and in anti-tumor immunity. We hypothesized that AFP might impair the ability of DC to stimulate natural killer T (NKT) cells. No significant impact of AFP was observed on NKT cell stimulation. By examining secreted cytokines, we observed non-significant AFP-induced changes in several secreted proteins. These data indicate that AFP downregulates CD1 molecules on DC, but the impact on NKT cell activations is minimal.